Mathematics Teaching Anxiety Scale: Construction, Reliability and Validity - Vesile Alkan; Yücel Fidan; Tolga Coşguner (International Journal of Assessment Tools in Education, 2019)
Thisstudy aimed to develop mathematics teaching anxiety scale for prospectiveprimary school teachers. It was designed based on survey method and conductedwith four sampling group consisting of 956 prospective primary school teachersat Education Faculties in Turkey. First sampling group was consisted of 404prospective primary school teachers and 96 out of it were involved in theapplication of open-ended questions and 308 were involved in exploratory factoranalysis. 305 prospective primary school teachers in the second sampling groupparticipated in the confirmatory factor analysis, 108 prospective teachers inthe third group were involved in criterion validity and 139 prospectiveteachers in the fourth one participated in the test-retest reliabilityanalysis. As a result of the principal component analysis of the MathematicsTeaching Anxiety Scale (MTAS), it was found that the scale indicating single factor structure and consisting of 31items (47.43% of the total variance). After suggested modifications, the scaleMTAS was constructed with 19 items. 12 items were removed from the scale andthe confirmatory factor analysis (CFA) was carried out with 19 items. Accordingto CFA results (0≤X2 / df = 1.483≤2, RMSEA = 0.040, RMR = 0.050, AGFI = 0.908,TLI = 0.972, CFI = 0.976, IFI = 0.976, GFI = 0.928, NFI = 0.930 and RFI =0.919), it was confirmed that the scale structure was consisting of 19 itemsand one dimension. Cronbach's alpha coefficient of the final form ofMathematics Teaching Anxiety Scale was calculated as 0.93.